Dydaktyczne walory nauki historii = Didactic values of history teaching history - Topolski, Jerzy (1928-1998) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author analyzes the didactic values of history teaching other than normally indicated educational results aiming at the shaping the political behaviour. Looking at that problem through the function of human thinking history can provide disciples' mentality with such properties as the dynamic and global (or integral) thinking. Other very important feature of the teaching of well written ( explanatory) history is the saturation of the mental attitudes with the nomothetic elements.
Keywords: dydaktyka historii